Bioenergetics of different sole and pigeonpea (Cajanus cajun) - based intercropping systems - Deka, J; Pal, M (The Indian Journal of Agricultural Sciences, 2012)
A field experiment was conducted during 1988 and 1989 to study bioenergetics of different sole and pigeonpea [Cajanus cajan(L.) MiIlsp.]-based intercropping systems at New Delhi. Pigeonpea intercropped with blackgram (Phaseolus mungo L.), pearlmillet [Pennisetum glaucum (L.) R. Br. emend. Stuntz). sorghum [Sorghum bicolor (L.) Moench) and cowpea [ Vigna unguiculata(L.) Walp.] increased energy yield respectively by 42.9, 37.7, 32.2 and 9.0% and solar-energy-utiIization efficiency by 44,39, 34 and 9.8% compared with sole pigeonpea. Energy productivity in sole pigeonpea was found 1.15 kg/M cal, whereas inpigeonpea intercropped with blackgram, pearl millet, sorghum and cowpea was 1.23, 0.73, 1.38 and 1.55 kg/Meal respectively.Intercropping pigeonpea with sorghum (189 K cal/Re), blackgram (213 K cal/Re) and cowpea (171 K cal/Re) was found less-energyintensive than sole pigeonpea (226 K cal/Re). Pigeonpea + blackgram intercropping was found the best for energy parameters,viz energy yield, solarenergy- utilization efficiency, cultural energy input, output: input ratio, energy productivity andenergy intensiveness.